2006
DOI: 10.1097/01.ta.0000195715.63978.80
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Has a Stronger Relation with Outcome in Trauma Patients than in Other Critically Ill Patients

Abstract: The relation of hyperglycemia and mortality is more pronounced in trauma patients than in SICU patients admitted for other reasons. The different behavior of hyperglycemia in these patients underscores the need for evaluation of intensive insulin therapy in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
1
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 43 publications
2
75
1
1
Order By: Relevance
“…There is some evidence that during an acute cardiovascular event patients with hyperglycaemia have a worse prognosis than normoglycaemic patients [12,13]. The same finding has been shown after trauma [14,15]. Notably, it has been shown that type 2 diabetic patients with postprandial hyperglycaemia are at increased risk of myocardial infarction and stroke [16][17][18].…”
supporting
confidence: 58%
“…There is some evidence that during an acute cardiovascular event patients with hyperglycaemia have a worse prognosis than normoglycaemic patients [12,13]. The same finding has been shown after trauma [14,15]. Notably, it has been shown that type 2 diabetic patients with postprandial hyperglycaemia are at increased risk of myocardial infarction and stroke [16][17][18].…”
supporting
confidence: 58%
“…This finding has important implications for the clinician, since the infusion of a large volume of D5W can sometimes result in a sizable glucose load in patients for whom hyperglycemia may be detrimental (e.g., brain injury, trauma). 11 Furthermore, it is now recognized that tight control of blood glucose levels may improve outcome in critically ill patients; thus critical care physicians are trying to avoid infusing glucose when deemed unnecessary. 11,15 Although this has important clinical implications, only one study has investigated the degradation of NE in NS using HPLC.…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, it is now recognized that tight control of blood glucose levels may improve outcome in critically ill patients; thus critical care physicians are trying to avoid infusing glucose when deemed unnecessary. 11,15 Although this has important clinical implications, only one study has investigated the degradation of NE in NS using HPLC. Studying concentrations of 4 and 8 µg·mL -1 , Baumgartner et al, 9 found that 98% of NE was still present after 24 hr, which is in agreement with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we used the hyperglycemic index to describe multiple glucose measurements taken at irregular sampling intervals over a period of time. The index represents the mean glucose level above 108 mg/dL and yields a better estimate of overall glucose control than a single value at admission or the highest value during the day 19,20 . The hyperglycemic index was calculated for each patient in our investigation.…”
Section: Definition Of Hyperglycemiamentioning
confidence: 99%